Phosphorus and potassium balance in soil under crop rotation and fertilization - Steiner, Fabio [UNESP]; Pivetta, Laercio Augusto [UNESP]; Castoldi, Gustavo [UNESP]; Silva de Mendonca Costa, Monica Sarolli; de Mendonca Costa, Luiz Antonio (Universidade Estadual de Londrina (UEL), 2012)
The use of crop rotation and manure application can provide sustainability for an agricultural production system by improving soil quality and increasing nutrient use efficiency. This study aimed to evaluate the effect of mineral, organic and mineral+organic fertilization on grain yield and on soil phosphorus and potassium balance, in two crop systems under no-till, with and without rotation of cover crops. The experiment was carried out from 2006 to 2008 on a clayey Rhodic Hapludox in Marechal Candido Rondon, Parana State, Brazil. The cropping sequence in the rotation system involving cover crops was black oat + hairy vetch + forage turnip/corn/pigeon pea/wheat/mucuna + brachiaria + sunn hemp, and in the succession system was wheat/corn/wheat/soybean. Organic and mineral+organic fertilizations consisted of the application of solely manure and manure combined with mineral fertilizer, respectively. Soil P and K balances were calculated after the second year of the experiment, up to a depth of 0.40 m. First year corn yields were higher in the crop succession system accompanied by mineral fertilization. In the second year, wheat and soybean yield did not vary between crop systems and nutrient sources, demonstrating the residual effect of crop rotation and manure use. Crop rotation with cover crops resulted in an increase in soil K levels by promoting the recycling of this nutrient in the soil. In both crop systems, the application of mineral and organic fertilizers - either in isolation or in combination - resulted in a negative soil P and K balance in the short term. This represents a threat to the sustainability of the agricultural production system in the long term, due to the depletion of soil nutrient reserves.
Keywords: Organic fertilization; fertilizer; cover crops; soil nutrient; no-till